Kepemimpinan Berbasis Amanat Agung: Paradigma Misioner bagi Kepemimpinan Gereja Kontemporer - Rajiman Andrianus Sirait; Stenly Reinal Paparang (STT Pelita Dunia, 2026)
The Great Commission constitutes a fundamental mandate for the Church to carry out the mission of God in the world. However, in practice, many churches experience mission stagnation due to leadership that is more focused on internal management rather than the mobilization of external mission. This study aims to analyze the concept of Great Commission–based leadership as a paradigm of mission-oriented church leadership. The research method employed is a qualitative approach through a literature review of contemporary missiological and Christian leadership scholarship. The findings indicate that Great Commission–based leadership possesses three primary characteristics: leadership centered on the authority of Christ, leadership oriented toward discipleship, and reproductive leadership expressed through missional sending. This paradigm positions church leaders not merely as organizational managers, but as mobilizers of faith communities to actively participate in the mission of God (missio Dei). Therefore, leadership rooted in the Great Commission becomes a strategic factor in revitalizing the Church’s missional orientation amid global social and cultural changes.